Reglamentación y plusganancias en el autotransporte urbano. El caso de Buenos Aires - Gutiérrez, Andrea (2016)
The purpose of this paper is to contribute a theoretical reflection about the regulation of the urban public transport system. We start from a presentation of the main theoretical approaches supporting the academic debate about the regulation, trying to analyze its conceptual definition in depth and to define the approach of the analysis. Then, through the use of political economy concepts, such as surplus profit and income, we examine the relationship between regulation and generation of accumulation differentials obtained by the operating companies. The empirical research refers to the case of Buenos Aires metropolitan public transport and shows the behavior of the economic equation defined by the regulation on the basis of data from actual companies in the system. The conclusion is that in strictly regulated urban public transport systems there may exist accumulation differentials originated in unproductive benefits directly generated by the regulation. Since these surplus profits obtained by the companies may be established as income, we propose their conceptualization as statutory income.